Penerapan Terapi Berkumur dengan Air Matang dalam Menurunkan Rasa Haus Pada Pasien Chronic Kidney Disease (CKD) yang Menjalani Hemodialisa - Reza Dwinof; Efitra Efitra; Yosi Suryarinilsih; Idrawati Bahar; Herwati Herwati (Poltekkes Kemenkes Padang, 2025)
Chronic Kidney Disease (CKD) is a progressive decline in kidney function, causing metabolic disturbances and fluid-electrolyte imbalance, which can lead to uremia. CKD patients are required to restrict fluid intake to prevent complications, but this often causes excessive thirst. One simple method to relieve thirst is mouth rinsing with boiled water. This study aimed to determine the effectiveness of mouth rinsing with boiled water in reducing thirst intensity among CKD patients undergoing hemodialysis. A descriptive design with a case report approach was employed. Nursing care was provided from April 16 to May 4, 2024, in the Female Internal Ward of Dr. M. Djamil General Hospital, Padang. The Visual Analogue Scale (VAS) was used to assess thirst intensity. The sample consisted of two CKD patients selected based on inclusion criteria. Results showed that mouth rinsing with boiled water effectively reduced thirst intensity, decreasing from moderate thirst (score 4–6) to mild (score 1–3), and from severe thirst (score 7–10) to moderate (score 4–6). This simple intervention is effective and can be recommended as a nursing action to reduce thirst, both in hospital settings and at home.